Detection of deoxynivalenol and T-2 toxin in feeds by gas chromatography with Electron Captured Detector - Widiastuti, R.; ., Indraningsih (Indonesian Journal of Animal and Veterinary Sciences, 2009)
Deoxynivalenol (DON) and T-2 toxin are trichothecene mycotoxins produced by Fusarium spp. may pose to threat animal health. This research was aimed to validate an analysis method for DON and T-2 toxin detection in feed using a gas chromatography with electron captured detector ECD (GC-ECD) and to study the contamination level of DON and T-2 toxin in feed. Samples were extracted with organic solvents and derivitized with DMAP and HFBA prior to the detection with GC. Both toxins can be detected simultaneously with satisfied validation with GC. Analysis for DON showed that 17 out of 24 corn samples were positive (0.450 to 1.126 mg/kg), none was positive for 20 rice husk samples and 1 out of 14 cattle feed samples was positive (0.043 mg/kg), whereas analysis for T-2 toxin showed that 2 out of 24 corn samples were positive (0.022 and 0.063 mg/kg), 14 out of 20 rice husk samples were positive (0.027 to 0.720 mg/kg) and 6 out of 14 cattle feed samples were positive (0.039 to 0.084 mg/kg). The study showed that DON and T-2 toxin can be detected using GC-ECD. Whereas, the analysis results from field samples showed that the feeds were still safe to be used for animal feed, however a routine surveillance is needed to minimize further potential hazards. Key words:Â  Deoxynivalenol, T-2 toxin, Gas Chromatography, Feeds